A Novel Approach in Evaluating the Impact of Vehicle Age on Road Safety - Török, Árpád (Promet - Traffic&Transportation, 2020)
This study examines the correlation between road accident casualties and the age of the vehicle, assuming that the age of vehicles and the improvements in their safety designs are related. The study evaluates the impact of the interrelationship between road segment characteristics and road accident type on vehicle age at the time of the accident (AVC). To analyse the nested relationship between these variables, a multinomial logistic regression (MML) model has been developed. The result of the analysis also duly finds that vehicle age has an emphatic role in the occurrence of accidents.